Analisis Probabilistik Kepuasan Guru Terhadap Sistem Absensi QR Code Menggunakan Naïve Bayes Pada Data Kuesioner - Irfan Fakhruddin; Abdul Rohman (Institut Teknologi Garut, 2026)
The study aims to predict the satisfaction outcomes of teachers at SMA 1 Purwantoro regarding the implementation of a web-based QR Code attendance system using the Naïve Bayes data processing method. With the rapid development of the digital era, particularly in education, institutions are required to utilize technology. However, one of the public high schools in Wonogiri still uses a conventional attendance system, which is considered inefficient and time-consuming. The method used by the authors for data processing is Naïve Bayes, an algorithm based on statistical probability and Bayes’ theorem to predict probabilities. Data collection was conducted through a Google Form questionnaire involving 20 respondents, covering aspects of ease of use, speed, reliability, and security. Based on the probability table calculations, the level of teacher satisfaction in using the QR Code attendance system can be categorized as predominantly satisfied, with 65% of respondents stating they are satisfied and 35% indicating dissatisfaction. Furthermore, the conditional probability analysis within the satisfied category shows that the ease of use aspect has a value of 0.92, speed 1.00, reliability 0.92, and security 1.00 based on the overall respondent data. From these findings, it can be concluded that the implementation of a web-based QR Code attendance system is considered capable of facilitating teachers and staff in managing student attendance processes. The system helps reduce delays in attendance recording and simplifies the process of entering attendance data more efficiently.